Developing Teachers’ Guide to Use Facebook Group in a Blended Writing Course (A Research and Development in IAIN Surakarta) - Roko Patria Jati (Register Journal, 2016)
This study aimed to investigate the existence and the quality of any teachers’ guides used for Writing Course in IAIN Surakarta as well as the level of need and related criteria for development. Besides, the developmental steps in developing new teachers’ guide (to use Facebook Group in a blended Writing Course) were also investigated. This research  was conducted in IAIN Surakarta by involving ten teachers and 115 students. The findings of this study were obtained through some qualitative techniques, such as interview, observation, document analysis, and FGD. As the results, it was found that among ten tertiary teachers, only one of them using teachers’ guide or book to teach in the Writing Course. However, nine of them stated their need on the proposed product and one stated his uncertainty. Further, the related supports were also shown by majority of the students involved. Afterward, the draft was developed by considering some suggested criteria of development. After being validated by the related expert, the product was then field tested involving three teachers and 48 students. Through the tryouts conducted, the level of feasibility on the procedure had improved significantly to more than 90%. Keywords: teachers’ guide, Facebook Group, blended Writing Course  ABSTRAKPenelitian ini bertujuan untuk mengkaji keberadaan serta kualitas dari buku panduan guru yang digunakan untuk matakuliah Writing di IAIN Surakarta serta tingkat kebutuhan dan kriteria-kriteria yang terkait pengembangan. Disamping itu, penelitian ini juga menginvestigasi langkah-langkah dalam mengembangkan buku panduan guru. Penelitian ini diselenggarakan di IAIN Surakarta dengan melibatkan 10 dosen dan 115 mahasiswa. Temuan dari penelitian ini diperoleh melalui sejumlah teknik kualitatif seperti wawancara, pengamatan, analisis dokumen dan FGD. Hasilnya, ditemukan bahwa dari 10 dosen tersebut hanya 1 orang yang memanfaatkan buku panduan guru dalam mengampu matakuliah Writing. Meski demikian, 9 orang merasa memerlukan produk tersebut sementara 1 sisanya masih belum pasti. Kebutuhan serupa juga ditunjukkan oleh kebanyakan siswa yang terlibat. Kemudian, draf dikembangkan dengan mempertimbangkan kriteria pengembangan yang disarankan. Setelah mendapatkan validasi pakar, produk diujikan dengan melibatkan 3 dosen dan 48 mahasiswa. Melalui ujicoba yang dilakukan, tingkat kelayakan prosedur meningkat secara signifikan di atas 90%. Kata kunci: pedoman guru, Facebook Group, mata kuliah Writing yang dicampur (blended)